(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
Metaphor is a powerful linguistic and cognitive tool used to understand one concept in terms of another. It is more than just a figure of speech - it reflects cultural norms, thought patterns, and worldview. This article explores the role and the usage of metaphors in language, highlighting similarities and differences in structure, meaning, and cultural significance.